2021
DOI: 10.1364/josab.411643
|View full text |Cite
|
Sign up to set email alerts
|

Polarization- and angle-insensitive ultrabroadband perfect metamaterial absorber for thermophotovoltaics

Abstract: We report an ultrabroadband perfect metamaterial absorber, comprising a two-dimensional array of a hemi-ellipsoid shaped metallo-dielectric multilayered structure. What we believe, to the best of our knowledge, is an unprecedented average absorbance of ∼ 99 % is theoretically demonstrated in the 300 to 4500 nm spectral range at normal incidence. We use 20 pairs of molybdenum–germanium metallo-dielectric layers with tungsten as the ground metal placed on a silicon substrate. Our des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…[ 385 ] A hemi‐ellipsoid shaped metal‐dielectric multi‐layer structure of BMA achieves an unprecedented 99% average absorption in the spectral range of 300–4500 nm at normal incidence. [ 386 ] Some multi‐layer stacked designs of BMAs possess a more specific configuration in terms of appearance, such as a metal‐dielectric (Ni/SiO 2 ) stacked BMAs with a half cylinder cross section, [ 387 ] where the average absorption of the device exceeds 90% at normal incidence in the visible spectrum. Zhao et al.…”
Section: Design Strategies Of Broadband Metamaterials Absorbersmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 385 ] A hemi‐ellipsoid shaped metal‐dielectric multi‐layer structure of BMA achieves an unprecedented 99% average absorption in the spectral range of 300–4500 nm at normal incidence. [ 386 ] Some multi‐layer stacked designs of BMAs possess a more specific configuration in terms of appearance, such as a metal‐dielectric (Ni/SiO 2 ) stacked BMAs with a half cylinder cross section, [ 387 ] where the average absorption of the device exceeds 90% at normal incidence in the visible spectrum. Zhao et al.…”
Section: Design Strategies Of Broadband Metamaterials Absorbersmentioning
confidence: 99%
“…[385] A hemi-ellipsoid shaped metal-dielectric multilayer structure of BMA achieves an unprecedented 99% average absorption in the spectral range of 300-4500 nm at normal incidence. [386] Some multi-layer stacked designs of BMAs possess a more specific configuration in terms of appearance, such as a metal-dielectric (Ni/SiO 2 ) stacked BMAs with a half cylinder cross section, [387] where the average absorption of the device exceeds 90% at normal incidence in the visible spectrum. Zhao et al presented a BMA consisting of a curved periodic metaldielectric stack, [388] where the visible to MIR region allows an expected incidence of transverse magnetic polarization waves with an average light absorption of about 90%.…”
Section: Vertical Design Strategies For Broadband Metamaterials Absor...mentioning
confidence: 99%
“…Under the assistance of the metal substrate as a reflecting mirror, it is easy to realize perfect absorption based on the resonance from each unit. With a thin thickness, a MA can be scaled to operate in different frequency bands from the microwave to the ultraviolet [6].The central working frequency can be adjusted by introducing some tunable materials or mechanisms [7], and the working bandwidth can also be designed to be broadband based on various mechanisms, especially by introducing several different resonant modes into one unit cell [8]- [12]. MAs have been applied in various areas, such as electromagnetic and infrared cloaking [13], [14], photoelectric detection and imaging [15]- [17], solar energy utilization [18]- [20] and sensitive sensing [21]- [23].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, based on the coupling of Mie scattering, electric dipole, and surface plasmon polaritons resonances, Yun et al proposed an ultrabroadband metamaterial absorber 22 . Chowdhary et al reported an ultra‐broadband perfect metamaterial absorber consisting of a two‐dimensional (2D) array of metal‐dielectric multilayer structures in the shape of a semi‐ellipsoid 23 . In the previous works, 24–26 polarization tunable multi‐band terahertz resonant absorbers were developed using anisotropic microstructure arrays.…”
Section: Introductionmentioning
confidence: 99%
“…22 Chowdhary et al reported an ultra-broadband perfect metamaterial absorber consisting of a two-dimensional (2D) array of metal-dielectric multilayer structures in the shape of a semi-ellipsoid. 23 In the previous works, [24][25][26] polarization tunable multiband terahertz resonant absorbers were developed using anisotropic microstructure arrays. However, few previous works have paid attention to polarization-independent ultra-narrowband absorbers in the optical communication band.…”
Section: Introductionmentioning
confidence: 99%